Bioprospecting of polyhydroxyalkanoates-producing bacteria from Indonesian marine environment - WATUMESA A TAN; IRA WIJAYA; TRESNAWATI PURWADARIA (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Tan WA, Wijaya I, Purwadaria T. 2019. Bioprospecting of polyhydroxyalkanoates-producing bacteria from Indonesian marine environment. Biodiversitas 20: 1309-1315. Polyhydroxyalkanoates (PHA) are potential alternates to conventional synthetic plastics. PHA production in bacteria involves PHA synthase gene encoded by phaC. In this study, we isolated PHA-producing bacteria from the coastline and 1 mile from the coastline of three beaches in Indonesia. Further phaC detection and characterization of PHA production were conducted. The isolates were subjected to phylogenetic analysis based on 16S rDNA. Red Nile staining on minimal agar revealed that twenty-three isolates showed orange fluorescent, which indicated that they accumulated PHA in their cells. PCR detection showed the presence of PHA synthase class I-encoding gene phaC in twelve isolates. One representative amplicon was sequenced to verify its identity, in which it shared 86% similarity with the PHA synthase class I-encoding gene from an uncultured bacterium. Interestingly, the production of PHA in isolate ST.PA.75, which was closely related to Vibrio sp., was 2.1-fold higher than that in the Ralstonia eutropha JMP134 control. Three isolates showed similarity with bacterial genera and/or species for which PHA producing phenotypes had never been described before TP.SWC.20, which was closely related to Microbacterium arborescens, as well as TP.SWC.33 and TP.SWC.85, which were similar to Psychrobacter spp. Phylogenetic analysis showed that the PHA producing isolates were clustered into three phyla: ?-Proteobacteria, Actinomycetes, and Bacilli. A majority of the isolates (75%) were related to ?-Proteobacteria. In this study, we uncovered diverse novel promising strains for use in the production of PHA as a more environmentally-friendly alternative to hydrocarbon-based plastics.